A large advanced freight aircraft: F-81 - Fielding, J. P. (Cranfield Institute of Technology, 1981)
Commercial air freight operations have grown in importance in recent years, due mainly to cost reductions caused by increasing aircraft and freight-terminal efficiencies. The bulk of this traffic is carried in the underfloor holds of wide-body passenger aircraft, but there is a significant sector of the market served by 'dedicated' freighters such as the 747F and DC8-63F. These aircraft are often equipped with standard containers and pallets which are loaded at factories or freight depots. The largest and most efficient container is the 8 ft x 8 ft x 20 ft size NASA felt the need to study the air-freight market and commissioned the extensive C.L.A.S.S. study (Ref.1). This report suggested that significant operating cost savings would be required, together with improved ground interfaces, to make more inroads into the surface transport market. It studied the economics of aircraft derived from current types, together with new designs. The former was more immediately attractive, but a market existed for new aircraft from the mid 1990's. The most attractive new type would be a long range aircraft with payload in the 75 to 165 ton range. The lower size aircraft was slightly more economic, but would pose grave airport frequency saturation problems and therefore a larger aircraft was preferable. Aircraft much above the 165 ton class however, would lead to development costs higher than the market could stand. An aircraft of about 165 tons payload seemed to be a good solution which could be made more attractive if it were designed to satisfy both civil and military requirements, thus spreading development costs. This philosophy was aimed at during the design of the Lockheed C-141 but too much emphasis was placed on military properties and no civil versions were sold. This should be avoided on a new design which should be capable of augmenting and partially replacing current fleets of 747F, DC10 CF and Lockheed C-5A aircraft … [cont.].